ANALISIS PENGELOLAAN LIMBAH B3 DARI FASILITAS PELAYANAN KESEHATAN DI PUSKESMAS SUNGAI SIRIH KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI - Hayana Hayana; Nila Puspita; Feri Razali (Ensiklopedia of Journal, 2021)
In Indonesia, the increase in health waste is around 70-90%, along with the increase in health service centers in Indonesia. This B3 waste comes from health agencies which are considered dangerous and can cause various types of health impacts. The production of solid medical waste from health services nationally in Indonesia is estimated at 376,089 tons/day. Kuantan Singingi Regency is in accordance with the guidelines for the Decree of the Minister of the Environment. The purpose of this research is to analyze the management of B3 waste at Sungai Sirih Community Health Center, Singingi District. This type of research is a qualitative survey, namely the method of interviews and field observations. The research subjects also involved in the management of B3 waste at Sungai Sirih Health Center, Singingi District, Kuantan Singingi Regency, namely, the Head of the Sungai Sirih Health Center, Singingi District, Kuantan Singingi Regency. Based on the results of research at the Sungai Sirih Health Center, Singingi District, Kuantan Singingi Regency in 2019, it was found that human resources in the B3 waste management process did not have a Standard Operating Procedure (SOP) at work and the facilities and infrastructure used were also inadequate and incomplete and there were no funds. or puskesmas budget in the process of B3 waste management at Sungai Sirih Health Center, so that the sorting process, collection process, storage process, transportation process, and landfill or burial process have not been carried out according to health requirements according to LHK Regulation No. 56 of 2015 concerning Procedures and Technical Requirements for the Management of Hazardous and Toxic Waste from Health Service Facilities.